Use of diagnostic ultrasound for assessing muscle size - Bemben, M. G. (The Journal of Strength and Conditioning Research, 2002)
The typical "gold standard" for assessing muscle size has been magnetic resonance imaging (MRI) and computerized tomography; however, these processes are very expensive and generally require a medical facility. The advent of B-mode diagnostic ultrasound (US) can perhaps offer a quick, cost-effective method to measure muscle size. The purpose of this study was to document the reliability of B-mode US for assessing muscle size in a variety of populations. Thirty-eight postmenopausal women (avg. age = 58.9 ± 0.7 years) had both their right rectus femoris and biceps brachii imaged, 85 older men and women (avg. age = 65.0 ± 0.4 yrs) had their right rectus femoris imaged, and 10 young men and women (avg. age = 26.1 ± 2.4 yrs) had their right rectus femoris imaged by both US and MRI. The location used for imaging on the right rectus femoris was a point 15 cm above to the superior border of the patella following the midline of the anterior surface of the thigh, whereas the biceps brachii was measured at maximal girth following the midline of the anterior surface of the upper arm. All trials utilizing US (Fukuda Denshi, model 4500) and a 5 Mz transducer (FUT-L104) were obtained in duplicate on 2 separate days. The young subjects that also had their rectus femoris measured by MRI were imaged with a Picker 1.5 Tesla (The Edge), which used a fast spin sequence and 192 × 256 resolution to obtain 25-mm-thick slices separated by a 1-mm-thick space. All intraclass correlation coefficients for the various groups and muscles measured by US ranged from r = 0.72-0.99, whereas coefficients of variation (CVs) ranged between 3.5% and 6.7%. The intraclass correlation for the MRI images was r = 0.90 and the CV was 5.2%. In conclusion, it appears that diagnostic US can provide a reliable and cost-effective alternative method for assessing muscle.